Study protocol for a pragmatic randomised controlled trial of comparing enhanced acceptance and commitment therapy plus (+) added to usual aftercare versus usual aftercare only, in patients living with or beyond cancer: SUrvivors’ Rehabilitation Evaluation after CANcer (SURECAN) trial - Imran Khan; Stephanie J. C. Taylor; Clare Robinson; Elisavet Moschopoulou; Paul McCrone; Liam Bourke; Mohamed Thaha; Kamaldeep Bhui; Derek Rosario; Damien Ridge; Sheila Donovan; Ania Korszun; et al. (Trials)
Abstract  Background Two million people in the UK are living with or beyond cancer and a third of them report poor quality of life (QoL) due to problems such as fatigue, fear of cancer recurrence, and concerns about returning to work. We aimed to develop and evaluate an intervention based on acceptance and commitment therapy (ACT), suited to address the concerns of cancer survivors and in improving their QoL. We also recognise the importance of exercise and vocational activity on QoL and therefore will integrate options for physical activity and return to work/vocational support, thus ACT Plus (+). Methods We will conduct a multi-centre, pragmatic, theory driven, randomised controlled trial. We will assess whether ACT+ including usual aftercare (intervention) is more effective and cost-effective than usual aftercare alone (control). The primary outcome is QoL of participants living with or beyond cancer measured using the Functional Assessment of Cancer Therapy: General scale (FACT-G) at 52 weeks. We will recruit 344 participants identified from secondary care sites who have completed hospital-based treatment for cancer with curative intent, with low QoL (determined by the FACT-G) and randomise with an allocation ratio of 1:1 to the intervention or control. The intervention (ACT+) will be delivered by NHS Talking Therapies, specialist services, and cancer charities. The intervention consists of up to eight sessions at weekly or fortnightly intervals using different modalities of delivery to suit individual needs, i.e. face-to-face sessions, over the phone or skype. Discussion To date, there have been no robust trials reporting both clinical and cost-effectiveness of an ACT based intervention for people with low QoL after curative cancer treatment in the UK. We will provide high quality evidence of the effectiveness and cost-effectiveness of adding ACT+ to usual aftercare provided by the NHS. If shown to be effective and cost-effective then commissioners, providers and cancer charities will know how to improve QoL in cancer survivors and their families. Trial registration ISRCTN: ISRCTN67900293 . Registered on 09 December 2019. All items from the World Health Organization Trial Registration Data Set for this protocol can be found in Additional file 2 Table S1.